PENGARUH PERTUMBUHAN ASSET DAN VOLUME PENJUALAN TERHADAP STRUKTUR MODAL DAN PENAHANAN KAS - Pradnyana Manuaba, Ida Bagus; Wiksuana, I G B; Wiagustini, Ni Luh Putu (Buletin Studi Ekonomi, 2016)
The Influence Of Firm Growth And Sales Volume On Capital Structure And Cash Holding. This research is aimed to explain the influence of firm growth and sales volume on capital structure and cash holding in mining companies listed in Indonesia Stock Exchange from 2008 until 2011.  Census method is used in this research. Researcher is using secondary data taken from Indonesia Capital Market Directory 2008-2012. The research hypothesis is tested by a path analysis. The result of this study shows that asset growth and sales volume has a positive and significant influence on capital structure, asset growth  and sales volume has a positive and significant influence on cash holding, capital structure has a negative and significant influence on cash holding, capital structure is not able to mediate the influence of asset growth and sales volume on cash holding.   Keywords: asset growth, sales volume, capital structure, cash holding
Keywords: asset growth, sales volume, capital structure, cash holding